Cardiac allograft vasculopathy after heart transplantation: Is it really ominous?. Issue 2 (12th January 2017) - Lim, Ju Yong; Jung, Sung Ho; Kim, Min Seok; Park, Jeong‐Jun; Yun, Tae‐Jin; Kim, Jae Joong; Lee, Jae Won
Abstract: Objectives: Cardiac allograft vasculopathy (CAV) remains a major impediment to long‐term survival after heart transplantation (HT). We investigated the incidence, disease course, and risk factors for CAV. Methods: Among 399 patients who underwent HT between November 1992 and July 2014, 297 survivors were reviewed. Endpoints were CAV development and the composite outcome of death or re‐HT. Results: During 5.6±5.2 years, CAV was detected in 54 patients: 45 (83.3%), 8 (14.8%), and 1 (1.8%) patients for CAV 1, 2, and 3, respectively. At 1, 5, and 10 years, 99.0%, 82.4%, and 60.3% of patients were free of CAV, respectively. Only four patients (7.4%) showed progression over 4.8±2.1 years' follow‐up. The presence of CAV did not affect the composite outcome ( P =.89). Predictors of CAV included donor age (HR1.06, 95% CI: 1.03‐1.10: P <.001), recipient age (1.03 [1.003‐1.06]; P =.03), ischemic time >240 minutes (3.15 [1.36‐7.28], P =.007), postoperative renal replacement therapy (RRT) (7.1 [2.3‐21.8]; P =.001), and triglyceride level at 1 year post‐HT (1.005 [1.002‐1.008], P =.003). Conclusions: CAV incidence after HT appears acceptable, with most cases being stationary and inconsequential for survival. Development of CAV seems to be influenced by donor and recipient age, ischemic time, postoperative RRT, and high triglyceride level.